Erythropoietin Does Not Alter Serum Profiles of Neuronal and Axonal Biomarkers After Traumatic Brain Injury: Findings From the Australian EPO-TBI Clinical Trial. Issue 4 (April 2018) - Hellewell, Sarah C.; Mondello, Stefania; Conquest, Alison; Shaw, Gerry; Madorsky, Irina; Deng, Jay V.; Little, Lorraine; Kobeissy, Firas; Bye, Nicole; Bellomo, Rinaldo; Cooper, David J.; Vallance, Shirley; et al.
Abstract : Objective: To determine profiles of serum ubiquitin carboxy-terminal hydrolase L1 and phosphorylated neurofilament heavy-chain, examine whether erythropoietin administration reduce their concentrations, and whether biomarkers discriminate between erythropoietin and placebo treatment groups. Design: Single-center, prospective observational study. Setting: A sub-study of the erythropoietin-traumatic brain injury clinical trial, conducted at the Alfred Hospital, Melbourne, Australia. Patients: Forty-four patients with moderate-to-severe traumatic brain injury. Interventions: Epoetin alfa 40, 000 IU or 1 mL sodium chloride 0.9 as subcutaneous injection within 24 hours of traumatic brain injury. Measurements and Main Results: Ubiquitin carboxy-terminal hydrolase L1, phosphorylated neurofilament heavy-chain, and erythropoietin concentrations were measured in serum by enzyme-linked immunosorbent assay from D0 (within 24 hr of injury, prior to erythropoietin/vehicle administration) to D5. Biomarker concentrations were compared between injury severities, diffuse versus focal traumatic brain injury and erythropoietin or placebo treatment groups. Ubiquitin carboxy-terminal hydrolase L1 peaked at 146.0 ng/mL on D0, significantly decreased to 84.30 ng/mL on D1, and declined thereafter. Phosphorylated neurofilament heavy-chain levels were lowest at D0 and peaked on D5 at 157.9 ng/mL. D0 ubiquitin carboxy-terminal hydrolase L1 concentrations were higher in diffuse traumatic brain injury. Peak phosphorylated neurofilament heavy-chain levels on D3 and D4 correlated with Glasgow Outcome Score–Extended, predicting poor outcome. Erythropoietin did not reduce concentrations of ubiquitin carboxy-terminal hydrolase L1 or phosphorylated neurofilament heavy-chain. Conclusions: Serum ubiquitin carboxy-terminal hydrolase L1 and phosphorylated neurofilament heavy-chain increase after traumatic brain injury reflecting early neuronal and progressive axonal injury. Consistent with lack of improved outcome in traumatic brain injury patients treated with erythropoietin, biomarker concentrations and profiles were not affected by erythropoietin. Pharmacokinetics of erythropoietin suggest that the dose given was possibly too low to exert neuroprotection.